The Effect of Regional Original Income, General Allocation Funds And Special Allocation Funds On Capital Expenditures - Nagara, Patria; Putri, Divia Amanda Eka; Yanti, Novi; Hendri, Novi (International Journal of Management and Digital Business, 2026)
This study aims to determine: (1) The Effect of Regional Original Income on Capital Expenditures, (2) The Effect of General Allocation Funds on Capital Expenditures, (3) The Effect of Special Allocation Funds on Capital Expenditures, (4) The Effect of Regional Original Income, General Allocation Funds and the Special Allocation Fund for Capital Expenditures in Cities in the Province of West Sumatra. The type of data used in this research is quantitative research. The population used in this study is all PAD, DAU, DAK and Capital Expenditure. The sample used is a saturated sampling technique or a sampling technique based on all cities in West Sumatra Province with a total of 7 cities. Collecting data from the report on the realization of the Regional Revenue and Expenditure Budget (APBD) of the city in West Sumatra Province and data processing techniques using Eviews 9. Based on the results of the study, it is shown that: (1) The results of the T test and the T table and T count test indicate that PAD has a significant effect on capital expenditure in cities in West Sumatra Province. (2) The results of the T-test and the T-table and T-value tests indicate that the DAU has a significant effect on capital expenditures in cities in the province of West Sumatra. (3) The results of the T-test and T-table and T-value tests indicate that DAK has a significant effect on capital expenditures in cities in West Sumatra Province. (4) The results of the F test and the Ftable and Fcount tests show that PAD, DAU, DAK have a significant effect on capital expenditures in cities in West Sumatra Province. And the coefficient of determination is known that the R-quare value is 0.941191 or 94%, meaning that capital expenditures can be explained by PAD, DAU, DAK by 94%. while the remaining 6% can be explained by other variables outside the study